2012
DOI: 10.3109/14992027.2012.690077
|View full text |Cite
|
Sign up to set email alerts
|

Societal costs of hearing disorders: A systematic and critical review of literature

Abstract: Acronyms and abbreviations:COI Abstract ObjectiveThe objective of this study was to perform a critical and systematic literature review of studies on societal costs due to hearing disorders. DesignWe used pre-defined search terms and inclusion/exclusion criteria. Systematic searches were conducted in Medline, Cochrane Library, Google scholar and other relevant websites. The review included studies written in English or Swedish between 1995 and the end of January 2012. Study sampleWe identified 4 published stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…The impact of the hearing healthcare access delay in rural residents on auditory outcomes and quality of life is unknown, and the key determinants in timely access to care are undefined. Thus far, substantial research has demonstrated the mental health, financial, and occupational impact of hearing impairment in the general adult population . Significant in our analysis was the inverse correlation between age at hearing loss and time to hearing aid acquisition.…”
Section: Discussionmentioning
confidence: 69%
“…The impact of the hearing healthcare access delay in rural residents on auditory outcomes and quality of life is unknown, and the key determinants in timely access to care are undefined. Thus far, substantial research has demonstrated the mental health, financial, and occupational impact of hearing impairment in the general adult population . Significant in our analysis was the inverse correlation between age at hearing loss and time to hearing aid acquisition.…”
Section: Discussionmentioning
confidence: 69%
“…Hearing loss is the most common sensorineural deficit in the elderly and it is estimated that 700 million persons have moderate to profound hearing loss worldwide in 2015, with approximately 30% of them occurred in their seventies and 50% in their eighties (Niklaus et al 2011;Hjalte et al 2012;Quaranta et al 2015). Age-related hearing loss (AHL) can lead to communication difficulties and cause social isolation, depression and anxiety, all of which severely influence the quality of life of patients (Ciorba et al 2012).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…In Sweden, 55 % of people with hearing impairment are of working age (18-65 years of age), and early retirement in this group is almost twice as high (9.3%) as for the general population (5.3%) which has significant societal costs (Hjalte, Brännström, & Gerdtham, 2012).…”
Section: Prevalence In Swedenmentioning
confidence: 99%